PENGARUH AKTIVITAS, PROFITABILITAS TERHADAP PERTUMBUHAN LABA (Studi Pada Perusahaan Otomotif dan Komponen Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Dwi Lathifah Sari; Siti Rosyafah; Masyhad (AKUNTANSI 45, 2021)
The company has the main objective of obtaining and increasing profits. The profits obtained by the company will be used for various purposes, one of which is used to improve the company's welfare for the products or services sold. This study aims to determine the effect of activity, profitability on profit growth in automotive and component companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with data collection using financial statements. The population of this study are automotive and component companies listed on the Indonesia Stock Exchange during the 2015-2019 period. The sampling technique used is purposive sampling technique. The data analysis method used is multiple linear regression analysis with hypothesis testing, namely the F test and t test. The results of this study indicate that activity, profitability have a simultaneous and partial effect on profit growth. Profitability variable has a dominant effect on Profit Growth.